The Procedural and Clinical Outcomes of Rotational Atherectomy in Patients Presenting With Acute Myocardial Infarction - Chen, Yu-Wei; Lai, Chih-Hung; Su, Chieh-Shou; Chang, Wei-Chun; Wang, Chi-Yen; Chen, Wei-Jhong; Lin, Tzu-Hsiang; Liang, Kae-Woei; Liu, Tsun-Jui; Lee, Wen-Lieng (Frontiers in Cardiovascular Medicine, 2022)
Background Rotational atherectomy (RA) is an indispensable tool used for calcified lesion preparation in percutaneous coronary intervention (PCI). However, use of RA in the setting of acute myocardial infarction (AMI) is challenged with limited clinical data. Objectives This study aims to retrospectively investigate the procedural results, periprocedural complications, and clinical outcomes of RA in patients with AMI. Methods All possible consecutive patients who received RA in AMI from January 2009 to March 2018 in a single tertiary center were analyzed retrospectively. Patients without AMI during the study period were also enrolled for comparison. Results A total of 121 patients with AMI (76.0 ± 10.8 years, 63.6% males) and 290 patients without AMI were recruited. Among the AMI group, 81% of patients had non-ST-elevation myocardial infarction (NSTEMI) and 14% presented with cardiogenic shock. RA could be completed in 98.8% of patients in the AMI group and 98.3% in the non-AMI group (p = 1.00). The periprocedural complication rates were comparable between the AMI and non-AMI groups. The risks of in-hospital, 30-day, 90-day, and 1-year cardiovascular major adverse cardiac events (CV MACE) were significantly higher in the AMI group compared with the non-AMI group (in-hospital 13.2 vs. 2.8%, p < 0.001; 30-day 14.2 vs. 4.5%, p < 0.001; 90-day 20.8 vs. 6.9%, p < 0.001; 1-year 30.8 vs. 19.1%, p = 0.01). AMI at initial presentation and cardiogenic shock were predictors for both in-hospital CV MACE and 1-year CV MACE in multivariable binary logistic regression analysis. Other predictors for 1-year CV MACE included serum creatinine level and triple vessel disease. Conclusion RA in patients with AMI is feasible with a high procedural completion rate and acceptable periprocedural complications. Given unstable hemodynamics and complex coronary anatomy, the in-hospital and 1-year MACE rates remained higher in patients with AMI compared with patients without AMI.